Eccrine Chromhidrosis in an Adolescent with Sickle Cell Disease. Issue 5 (30th July 2017) - Park, Jong G.; Prose, Neil S.; Garza, Reed
Abstract: Eccrine chromhidrosis can occur secondary to hyperbilirubinemia. We report an adolescent with sickle cell disease who presented with eccrine chromhidrosis on his palmar and plantar surfaces. He had extremely high levels of conjugated bilirubin but no fever. This is the youngest known reported patient with eccrine chromhidrosis and the first in a patient with sickle cell disease.